Indigenous people's resilience on the issue of the Indonesian capital move - Badruddin Nasir; Lisbet Situmorang; Reynaldi Poppy Latief (Jurnal Studi Komunikasi, 2023)
The Paser and Kutai Indigenous People will be affected by the Indonesian New Capital (IKN) move. This study examines how citizens adapt to the new capital city (IKN) culture. This research showed how the Paser and Kutai Indigenous People were able to transfer the national capital and what options may be taken to make their customs more active and known internationally. Literature review. Documentation-based data collecting. Miles and Huberman's interactive analysis is applied. This study found that the Paser and Kutai Indigenous Peoples are self-sufficient and ready to move the national capital. The transfer of the National Capital (IKN) to North Penajam Paser (PPU) and Kutai Kartanegara (Kukar) has improved local culture through acculturation. To be beneficial, this acculturation must filter out external cultural ideals that contradict local wisdom. Becoming the national capital is a great chance to showcase local culture abroad. Regional Regulation No. 2 of 2017 concerning the Preservation and Protection of Paser Customs and Regional Regulation No. 2 of 2016 concerning the Preservation of the Customs of the Kutai Kartanegara Ing Martadipura Sultanate also preserve Paser and Kutai's local culture.